Pedagogical Image Components in the Modern Professional Profile of School Teachers - Bobir qizi , Doniyorova Gulbahor (Journal of Innovation in Education and Social Research, 2024)
Talking about the modern professional profile of school teachers, pedagogical image components play a crucial role in shaping their effectiveness and impact on students. These components encompass various aspects that contribute to a teacher's overall image as an educator. Let's dive into some key components.